Myeloid Derived Suppressor Cells in Chronic Myeloid Leukemia - Giallongo, Cesarina; Parrinello, Nunziatina; Brundo, Maria Violetta; Raccuia, Salvatore Antonino; Di Rosa, Michelino; La Cava, Piera; Tibullo, Daniele (Frontiers in Oncology, 2015)
The suppression of the immune system create a permissive environment for development and progression of cancer. One population of immunosuppressive cells that have become the focus of intense study is myeloid derived suppressor cells (MDSCs), immature myeloid cells able to induce immune-escape, angiogenesis and tumor progression. Two different subpopulations have been identified and studied: granulocytic and monocytic MDSCs, with a different immunophenotype and immunosuppressive properties. Recently, an accumulation of both Gr-MDSCs and Mo-MDSCs cells has been found in the peripheral blood of chronic myeloid leukemia (CML) patients. They are part of the tumor clone showing BCR/ABL expression. Imatinib therapy decreases both MDSCs and arginase 1 levels to normal ones. This review will focus on actual knowledge for human MDSCs and their immunosuppressive activity in CML patients with a critical attention to comparison of Gr-MDSCs and polymorphonuclear cells (PMNs). We will then suggest the monitoring of MDSCs in patients who have discontinued tyrosine kinase inhibitors (TKIs) therapy to evaluate if their increase could correlate with disease relapse.